2015
DOI: 10.1080/15384101.2015.1012875
|View full text |Cite
|
Sign up to set email alerts
|

Cell divisions are not essential for the direct conversion of fibroblasts into neuronal cells

Abstract: These authors equally contributed to this work.Keywords: cell division, direct conversion, fibroblast, neuron, reprogramming, transdifferentiation Abbreviations: iPS cells, induced pluripotent stem cells; ES cells, embryonic stem cells; BAM, Brn2, Ascl1 and Myt1l; BAMCM, Brn2, Ascl1, Myt1l and cMyc; DOX, doxycycline; BrdU, bromodeoxyuridine; MEF, mouse embryonic fibroblasts.Direct lineage conversion is a promising approach for disease modeling and regenerative medicine. Cell divisions play a key role in reprog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Although it has not yet been decisively demonstrated whether fibroblast-based iNs pass through an intermediate progenitor-like epigenetic state (as studies based on glia as starting cells suggest 104,105 ), it is well established that iN conversion requires no proliferation 98,106 . Cell division is deemed essential during in vivo and hPSC differentiation because it stimulates the chromatin remodelling required to provide transcription factor access to previously closed regions 92 .…”
Section: Direct Conversion To Neural Cellsmentioning
confidence: 99%
“…Although it has not yet been decisively demonstrated whether fibroblast-based iNs pass through an intermediate progenitor-like epigenetic state (as studies based on glia as starting cells suggest 104,105 ), it is well established that iN conversion requires no proliferation 98,106 . Cell division is deemed essential during in vivo and hPSC differentiation because it stimulates the chromatin remodelling required to provide transcription factor access to previously closed regions 92 .…”
Section: Direct Conversion To Neural Cellsmentioning
confidence: 99%
“…However, direct reprogramming has clearly demonstrated that proliferation is not a prerequisite for the cell fate switch, as many cell types can convert into neurons without cell division (Fishman et al, 2015;Gascón et al, 2016;Heinrich et al, 2010;Karow et al, 2012;Marro et al, 2011). In fact, the overexpression of the cell cycle activator Myc actually reduced the efficiency of fibroblast conversion to neuronal cells (Fishman et al, 2015).…”
Section: Peripheral Sensory Neuronsmentioning
confidence: 99%
“…However, direct reprogramming has clearly demonstrated that proliferation is not a prerequisite for the cell fate switch, as many cell types can convert into neurons without cell division (Fishman et al, 2015;Gascón et al, 2016;Heinrich et al, 2010;Karow et al, 2012;Marro et al, 2011). In fact, the overexpression of the cell cycle activator Myc actually reduced the efficiency of fibroblast conversion to neuronal cells (Fishman et al, 2015). This supports the observation that BETbromodomain inhibitors enhance neuronal reprogramming mediated by small molecules (Hu et al, 2015;Zhang et al, 2015), as these compounds cause cell cycle arrest and inhibit Myc expression at transcriptional levels (Cheng et al, 2007;Delmore et al, 2011;Gallagher et al, 2014).…”
Section: Peripheral Sensory Neuronsmentioning
confidence: 99%
“…While cells which completed transdifferentiation process stay as epithelial cells, other cells which are still undergoing the process can return back to hepatocyte fate if stimulus is removed (Tarlow et al 2014). Lastly, while cell division seems to be a critical requirement and an enhancing condition during iPSCs reprograming (Hanna et al 2009), it is not required during transdifferentiation of fibroblasts into neural cells (Iwafuchi-Doi et al 2014;Fishman et al 2015).…”
Section: Reprograming Reverses Differentiation To Generate Pluripotenmentioning
confidence: 99%